Evaluating the GET electrical technology syllabus for transition into FET specialisations in Gauteng Technical Schools - Dayi, Nzaliseko; Mtshali, Thokozani Isaac; Sephokgole, Ramongwane Daniel (Jurnal Inovasi Teknologi Pendidikan, 2026)
This study examined the General Education and Training (GET) syllabus of Electrical Technology to determine its effectiveness in preparing learners for progression into Further Education and Training (FET) specialisations in Gauteng technical schools. The problem this research addresses is the persistent misalignment between the foundational competencies developed in the GET phase and the advanced technical expectations of the FET phase, leaving learners underprepared for specialisation. The purpose of the study was to explore how the GET curriculum supports or fails to support smooth curriculum transition in Electrical Technology. A qualitative case study design was employed, using document analysis and semi-structured interviews with eleven experienced teachers in Gauteng Province, South Africa. The findings revealed that the GET curriculum is mostly theoretical, with limited practical scaffolding and weak sequencing of advanced topics such as Three-phase motors and Transformers. Teachers noted repeatedly re-teaching basic concepts at the FET level, which created time pressures and contributed to learner frustration. The study concludes that improving vertical curriculum alignment through stronger practical integration and clearer teacher support mechanisms can enhance learner readiness, curriculum coherence and the overall quality of Vocational Education (VOC) in South Africa.